Establishment of Reference Interval and Decision Limits (C-RIDLs) for routine and special Biochemical Parameters in healthy Nepalese volunteers aged (18-65) years - Mahato, Ram Vinod; Dutta, Ananta Madhab; Lamsal, Madhab; Ichihara, Kiyoshi (Journal of Ayurveda Campus, 2024)
Background: A national multicenter study was planned to derive reference intervals (RIs) in Nepalese healthy volunteers for 30 commonly tested biochemical analytes and to explore sources of variation in reference values. Materials and Method: Healthy subjects (n = 617), age ≥18 to ≤65 years old, were enrolled on the basis of the global study protocol. Blood samples were collected, serum was separated, and then sera were collectively analysed in Yamaguchi University, Department of Laboratory Medicine, Ube, Japan, using Beckman Coulter reagents and an AU 480 analyzer. Multiple regression analysis and two-level nested ANOVA were applied to derive reference intervals and analyse the source of variations. Results and Discussion: Gender, age at ≤45 and ≥ 45 years old, and partial regression coefficient (rp) ≥ 0.2 were considered for derivation of RIs and calculation of source of variations. RIs for serum total cholesterol and fractional cholesterols, urea, and ALT were found to shift conspicuously to the lower side. Whereas, UL of RIs for LDH and CK were shifted to the higher side. Conclusion: RIs valid for the Nepalese population were established for the majority of biochemistry parameters. Age and gender partitioning were required for some analytes. RIs derived from this nationwide study can be applicable for (18-65) age groups. It is not applicable for <18 and >65 years of age.